The Digitalization of Islamic Da’wah through the Utilization of Digital Qur’an Among Generation Z in Muncan Village - Anam, Khaerul; Winengan, Winengan (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
Although digital media increasingly shape Islamic practices and da’wah, limited scholarly attention has been paid to how Generation Z engages with digital Qur’an applications in rural contexts. This study aims to examine how Generation Z in Muncan Village interprets, experiences, and utilizes digital Qur’an applications as tools for both personal spirituality and religious propagation. Employing a qualitative case study design, the research involved 28 purposively selected participants aged 18–25 who actively used applications such as Quran Best, Muslim Pro, and Ayat. Data were gathered through participant observation, in-depth interviews, and documentation, and analyzed using Miles, Huberman, and Saldana’s interactive model—comprising data condensation, data display, and conclusion drawing. The findings indicate that digital Qur’an applications are perceived by Generation Z as both practical and spiritually enriching, facilitating daily worship, comprehension, reflection, and the cultivation of hybrid religiosity. Key factors influencing engagement include technological accessibility, social interaction, intrinsic spiritual motivation, and user-centered design. Despite these advantages, challenges such as digital distractions and emotional attachment to the printed mushaf persist. Additionally, the use of these applications has transformed Islamic da’wah into a participatory and ethically conscious digital practice, wherein individual acts of devotion extend into online sharing and peer-supported religious engagement. The study concludes that digital Qur’an applications significantly enhance recitation, understanding, and expressions of digital piety, reflecting a broader transformation in contemporary Islamic observance. These findings contribute to the theoretical development of digital religiosity and offer actionable insights for educators, da’i, and application developers in advancing inclusive and context-sensitive digital da’wah strategies. Future research should investigate long-term usage patterns and comparative rural–urban dynamics.